Movements, fronts, and social collectives: permanencies and updates: - Lusa, Mailiz Garibotti; Martinelli, Tiago (Argumentum, 2024)
The article deals with the dynamics of the organisation and actions of social movements in Porto Alegre/RS (Brazil). It analyses their demands to raise the visibility of social struggles allied in defence of social rights. It discusses the results of exploratory documentary research based on a sample taken from 2010 to 2019. Within this sample, activities were monitored and data collection and analysis of material relating to 20 collective organisations was undertaken. The results show that these organisations developed strategies to fulfil their purposes; that the representatives did not have their activities suspended or closed during the pandemic because they employed remote strategies. It is concluded that the struggle for the guarantee of social rights must continue and be maintained through the links and actions carried out.